Tathbiq Thoriqoh Muhādatsah Yaumiyah Li Tanmiyah Mahārah al Kalām Li Tholibāt al Ma’had Tebuireng Lil Banāt Jombang - Werdeh; Isniyatun Niswah (EL-FUSHA: Jurnal Bahasa Arab dan Pendidikan, 2024)
This research aims to determine the implementation of the Muhadastah Yaumiyah Method to Improve the speaking ability of Santri at the Tebuireng Putri Jombang Islamic Boarding School. The type of research used is a qualitative method which is carried out in detail on an object in the field. Analysis technique by systematically compiling data obtained from interviews, field notes, and documentation by organizing data into categories and making conclusions. Data collection through observation, interviews and documentation. The results of the research show that 1. The application of the muhadasah method at the Tebuireng Putri Jombang Islamic Boarding School is very good in the activities and learning applied in daily activities (2) The problem in the process of implementing the Muhadastah Yaumiyah method is the lack of demands and motivation of female students in learning Arabic . Not all teachers who teach at the Tebuireng Putri Islamic Boarding School are proficient in Arabic, and the methods are still monotonous, study time is limited, and media is minimal. 3. The solution used to overcome daily learning problems at school is to provide more motivation to students and give punishment to students who do not use Arabic when speaking and choose teachers who have Arabic language skills to hold other programs to increase maharah kalam by updated and interesting media.